ANALYSIS OF CONSUMER PROTECTION AGAINST DEFAULT DUE TO AGREEMENT ON MISUSE OF PERSONAL DATA BY ONLINE DRIVERS - Eni Surinda Siregar; Nuraliah Ali; Suriansyah Murhaini; Kristian (RADJA PUBLIKA, 2026)
Study This aim For knowing description protection consumer to breach of contract committed by online drivers against misuse of personal data with method analyze protection consumer in practice in fact as well as responsibility answer perpetrator to consumers who feel dissatisfied​ safety , discomfort , and loss for consumers . The research techniques used is method juridical normative with approach legislation and conceptual . Research results show that mismatch driver identity is form default Because performance No implemented in accordance with agreement electronics . As a result law from default the violate right consumer on security , comfort and certainty law as arranged in Constitution Protection Consumers , so that open room accountability for drivers.